A combination strategy of functionalized polymer coating with Ta ion implantation for multifunctional and biodegradable vascular stents - Kwang-Hee Cheon; Cheonil Park; Min-Ho Kang; Suhyung Park; Jinyoung Kim; Seol-Ha Jeong; Hyoun-Ee Kim; Hyun-Do Jung; Tae-Sik Jang (Journal of Magnesium and Alloys, 2021)
Biodegradable stents made of magnesium (Mg) and its alloys have been developed to minimize persistent inflammation or in-stent restenosis, which are the main problems for permanent stents. However, their rapid corrosion behavior under physiological conditions leads to poor vascular compatibility and premature structural failure, which remains an important unsolved clinical problem. Herein, we demonstrate a new strategy for solving this problem by combining poly (ether imide) (PEI) coating and subsequent tantalum (Ta) ion implantation. The PEI coating covers the whole surface of the Mg stent uniformly via a spray coating technique and provides Mg with superior corrosion resistance and stable sirolimus-carrying ability. Ta ion implantation is conducted by a sputtering-based plasma immersion ion implantation technique only onto the luminal surface of the PEI-coated Mg stent. Its extremely short processing time (< 30 s) permits preservation of the PEI coating's corrosion protection ability and sirolimus loading characteristics. In addition, a Ta-implanted skin layer that forms on the topmost surface of the PEI coating plays an effective role in not only preventing a rapid release of sirolimus from the surface but also improving the PEI coating's surface hydrophilicity. Based on in vitro cellular response and blood compatibility tests, Ta ion implantation leads to the improvement of endothelial cell adhesion/proliferation and suppression of platelet adhesion/activation regardless of sirolimus loading. These results indicate that the combination of PEI coating and Ta ion implantation has significant innovative potential to provide excellent vascular compatibility and prevent in-stent restenosis and thrombosis.